ISTHMOCELE: MODERN TREATMENT AND CORRECTION STRATEGIES - Malika R. Khikmatullayeva; Sanjar K. Yuldashev (Central Asian Journal of Medicine, 2024)
Caesarean section is one of the most frequently performed obstetric procedures. In recent decades, there has been a more than twofold increase in its frequency, which now amounts to approximately 24%. In this regard, the issue of the strength of the uterine scar after a cesarean section, as well as the impact of this scar on the course of subsequent pregnancies and childbirth, becomes especially important. This article presents a unique clinical case of isthmocele of significant size in a woman of young reproductive age. Taking into account the emerging symptoms that cause concern in the patient, a decision was made to perform metroplasty using minimally invasive gynecological methods.